The Doomsday Project, Deep Events, and the Shrinking of American Democracy - Peter Dale Scott (Japan Focus)
In recent years I have become more and more concerned with the interactions between three important and alarming trends in recent American history. The first is America's increasing militarization, and above all its inclination, even obsession, to involve itself in needless and pernicious wars. The second, closely related, is the progressive shrinking of public politics and the rule of law as they are subordinated, even domestically, to the requirements of covert U.S. operations abroad.The third, also closely related, is the important and increasingly deleterious impact on American history and the global extension of American power, of what I have called deep events. These events, like the JFK assassination, the Watergate break-in, or 9/11, which repeatedly involve law-breaking or violence, are mysterious to begin with, are embedded in ongoing covert processes, have consequences that enlarge covert government, and are subsequently covered up by systematic falsifications in media and internal government records.One factor linking Dallas, Watergate, and 9/11, has been the involvement in all three deep events of personnel involved in America's highest-level emergency planning, known since the 1980s as Continuity of Government (COG) planning, or more colloquially as "the Doomsday Project." The implementation of COG plans on 9/11, or what I call Doomsday Power, was the culmination of three decades of such planning, and has resulted in the permanent militarization of the domestic United States, and the imposition at home of institutions and processes designed for domination abroad.Writing about these deep events as they occurred over the decades, I have been interested in the interrelations among them. It is now possible to show how each was related both to those preceding it, and those which followed.